Antusiasme Politik Masyarakat Kota Palembang Pada Pimilihan Presiden Tahun 2019 - Indah Permata Sari; Yenrizal Yenrizal; Mariatul Qibtiyah (Prodi Ilmu Politik FISIP Universitas Islam Negeri Raden Fatah Palembang, 2022)
This study analyzes the Political Enthusiasm of the People of Palembang City in the presidential and vice presidential elections in 2019. This study aims to find out how the motives of the political enthusiasm of the people of Palembang City in the 2019 presidential and vice presidential elections and to find out how relevant the enthusiasm and political behavior of the people of Palembang City is. in the 2019 presidential and vice-presidential elections. The research method used is descriptive qualitative and the data sources in this study were obtained from the experiences of several figures in Palembang City and some people in Palembang City. Data were collected by observation, in-depth interviews, and documentation with technical analysis of data collection, data reduction, data presentation and drawing conclusions. The results of the research on the 2019 presidential and vice presidential elections in Palembang City showed the level of enthusiasm in the form of experiences that gave rise to various motives from the community and Because of Motive or motives that became the motives that dominated the enthusiasm of the people of Palembang City in the form of experiences shown through the role of the family, socialization of several important figures and General Election Commissions Palembang City institutions as well as the similarity of vision and mission with the leaders all influence the community in voting. Political behavior is divided into radical, moderate and status quo, conservative and liberal. The people of Palembang City are included in the type of radical political behavior that wants a change quickly in the form of people who are dissatisfied with the current government by voicing the #gantipresiden2019 Action which is an act of extreme political behavior. The relevance of intentions or motives also encourages people to carry out a political behavior to maintain, require a change and respond to the existing conditions in the 2019 presidential election. Keywords : Enthusiasm, Motives, Political Behavior. presidential election.